Situation Report: Poland, 30 January 1981 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Joint Government-Episcopate Commission Resumes Work A Historic Debate on Polish Television Mounting Unrest among Students Politburo and UPP Issue Join Guidelines for Agriculture Differences Persist over Censorship Reform Can Poland Afford EEC Aid? Scout Leaders Demand Return to Basics Second Congress of Peasant Self-help Cooperatives More about Pollution